Effect of Single Walled Carbon Nanotube as Counter Electrode on Laser-deposited Fe2O3 and TiO2 Films Solar Cells (Journal of Scientific Research, 2009)
Laser-deposited Fe2O3 films or dye-fixed TiO2 films were prepared for solar cells. For both the cells, a single walled carbon nanotube (SWNT) film or a Pt-loaded SWNT film, prepared by simply pasting over ITO glass, was used as a counter electrode. Stable current (I)-voltage (V) curves were found under UV-visible light irradiation using water containing KI and I2 as an electrolyte. A comparison of I-V curves was made for Pt alone and SWNT alone films used as a counter electrode. Almost similar efficiency was found by using both types of counter electrodes. However, enhanced efficiency was obtained for the Pt-loaded SWNT-film counter electrode.Keywords: TiO2; Fe2O3 film; Solar cell; SWNT.© 2009 JSR Publications. ISSN: 2070-0237(Print); 2070-0245 (Online). All rights reserved.DOI: 10.3329/jsr.v1i3.2631      J. Sci. Res. 1 (3), 430-437 (2009)